2021
DOI: 10.1038/s41398-021-01753-5
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation and emotional responses during the COVID-19 pandemic

Abstract: The impact of the COVID-19 pandemic on population mental health is of global concern. Inflammatory processes are thought to contribute to mental ill-health, but their role in experiences of psychological distress during the pandemic has not been investigated. We tested the hypothesis that elevated inflammatory biomarkers (high-sensitivity plasma C-reactive protein [CRP] and plasma fibrinogen) measured pre-pandemic would be positively predictive of increased depressive symptoms experienced during the pandemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 55 publications
(54 reference statements)
2
16
1
Order By: Relevance
“…No associations were observed between CRP and depression or anxiety. This contradicts a recent ELSA study that identified a relationship between pre-pandemic CRP and depression during the pandemic among older adults [74]. These discrepancies may be due to the current study having a smaller sample size and a larger time gap between the CRP and depression assessments.…”
Section: Discussioncontrasting
confidence: 90%
“…No associations were observed between CRP and depression or anxiety. This contradicts a recent ELSA study that identified a relationship between pre-pandemic CRP and depression during the pandemic among older adults [74]. These discrepancies may be due to the current study having a smaller sample size and a larger time gap between the CRP and depression assessments.…”
Section: Discussioncontrasting
confidence: 90%
“…Whilst poorer mental health was seen throughout the pandemic, it is difficult to link causally to COVID-19 infection, owing to the many, varied other factors associated with the pandemic that could have an impact on an individual's mental well-being. Hamilton et al (2021) , however, found that higher levels of inflammation seen in COVID-19 increase the vulnerability of older people to impaired mental health. An observational study by Magnusdottir et al ( Magnúsdóttir et al, 2022 ) also found that severe acute COVID-19 illness is associated with long term mental health morbidity.…”
Section: Discussionmentioning
confidence: 94%
“…The relationships between emotional distress and inflammation were also highlighted in the course of the COVID-19 pandemic [ 78 ]. Alterations in the mental status (i.e., anxiety and depression) present in COVID-19 inpatients were related to higher levels of inflammatory cytokines [ 79 ] and, in particular, showed a clear immune dysregulation recognized from the neutrophil/lymphocyte ratio, which was higher, while IL-10, major anti-inflammatory cytokine, and total lymphocyte counts were lower, compared with not having psychological symptoms [ 80 ].…”
Section: Psyche and Biological Systems: The Bidirectional Pathwaysmentioning
confidence: 99%
“…Immune dysregulation is particularly dangerous in a viral pandemic, such as COVID-19 [ 109 ]. An experimental study on adult macaques placed in solitary confinement for two weeks, which mimicked human lockdown, showed, already within the first 48 h, a marked reduction in all circulating immune cell populations, and the down-regulation of type I interferon (IFN) anti-viral gene expression [ 78 ].…”
Section: Mental States and Molecular Biologymentioning
confidence: 99%